Dampak Kenaikan Harga BBM Terhadap Masyarakat Kelas Bawah Di Kecamatan Rumpin Setelah Pandemi COVID 19 - Asep Riandi; Aep Saefullah; Zubair Arza (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The rise in fuel prices over the past two years has considerably impeded Indonesian society's present economic recovery following the Covid-19 outbreak. Fuel oil, often known as BBM, is a fuel produced by refining crude oil deep inside the ground. This study intends to explore how the covid 19 pandemic affected lower-class residents of the Rumpin sub-district by raising fuel prices. The case study approach method is used in this study's qualitative investigation. The lower class community is the focus of the study. The study's findings and analysis demonstrate how claustrophobic the lower-class community in Rumpin District is despite the fact that this fuel is essential for movement. so that fuel will still be bought despite the price hike. According to the study's findings, the government's experience with inflation compelled them to adopt a policy of raising fuel prices.